KOMITMEN ORGANISASI DAN KOMPENSASI DALAM MEMPENGARUHI TURNOVER INTENTION PADA KARYAWAN PT BERSAMA ZATTA JAYA PASCA COVID-19 - Gunawan Gunawan (STIE Mahardhika, 2023)
Challenges in the industrial world related to employee turnover continue to occur until after the Covid-19 pandemic. Early indications of employee turnover can be predicted from organizational commitment and employee competence. The purpose of this study is to obtain the results of an analysis of the effect of organizational commitment and compensation on employee turnover of PT Bersama Zatta Jaya (Elzatta Hijab) both partially and simultaneously. This study uses quantitative research methods and uses path analysis as a hypothesis test, this is supported by data collection based on interviews, surveys and distribution of questionnaires to respondents. The population in this study were all employees of PT Bersama Zatta Jaya (Elzatta Hijab), with research sampling identifying employees who had an intention to leave the company. The population was too large using the slovin formula so that 211 respondents were obtained. The results showed that organizational commitment to turnover intention. in the Elzatta Hijab company was very low. Influencing factors include structured career development opportunities and a supportive work environment. Meanwhile, compensation has a fairly high influence, with the importance of fairness in salary and performance-based incentive programs. Simultaneously, organizational competencies also play an important role in influencing turnover intention. Overall, reducing employee turnover is a challenge that companies must face. However, by paying attention to factors such as organizational commitment, compensation, and career development, companies can reduce turnoverrates and create a stable and productive work environment.